Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jonm.12589
|View full text |Cite
|
Sign up to set email alerts
|

Extent of compassion satisfaction, compassion fatigue and burnout in nursing: A meta-analysis

Abstract: In nursing, the prevalence rates of compassion fatigue and burnout are high. Better education and training may have a moderating effect on compassion fatigue and burnout and could improve the quality of life of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
202
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(254 citation statements)
references
References 37 publications
10
202
2
10
Order By: Relevance
“…Given current concerns surrounding stress and burnout among professionals in medicine and health sciences,100–105 a need exists to identify and implement sustainable programming for cultivating resilience. Five well-described programmes evaluated the impact of NM education on resilience and burnout detection and/or mitigation 22 39 50 70 81 90.…”
Section: Discussionmentioning
confidence: 99%
“…Given current concerns surrounding stress and burnout among professionals in medicine and health sciences,100–105 a need exists to identify and implement sustainable programming for cultivating resilience. Five well-described programmes evaluated the impact of NM education on resilience and burnout detection and/or mitigation 22 39 50 70 81 90.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing is a compassionate profession. When caring for patients, nurses may experience either compassion satisfaction or burnout (Zhang et al, 2018). Compassion satisfaction is a positive aspect that embodies a feeling of self-appreciation when caring for and helping others (Zhang et al, 2018); burnout is related to hopelessness and apathy and hinders an individual's ability to perform his or her job effectively (Khamisa, Oldenburg, Peltzer, & Ilic, 2015;Stamm, 2009).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…When caring for patients, nurses may experience either compassion satisfaction or burnout (Zhang et al, ). Compassion satisfaction is a positive aspect that embodies a feeling of self‐appreciation when caring for and helping others (Zhang et al, ); burnout is related to hopelessness and apathy and hinders an individual's ability to perform his or her job effectively (Khamisa, Oldenburg, Peltzer, & Ilic, ; Stamm, ). Compassion satisfaction and burnout in nursing work are influenced by nurses’ personal characteristics and affect their job satisfaction and well‐being (Kim & Yeom, ; Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On May 28,2019, the World Health Organization (WHO) declared in the 11th revision of the International Classi cation of Diseases (ICD-11) that burnout is a "professional phenomenon", and it is a syndrome caused by "chronic workspace stress that has not been successfully managed" [12]. Studies show that burnout is related to a series of self-reported physical and psychological stress indicators such as anxiety and depression [13], fatigue [14]. This situation should be taken seriously.…”
Section: Introductionmentioning
confidence: 99%